Limiting factors for the development of the Serbian hospitality industry - Nikolina Kosar; Sasa Masic; Lidija Barjaktarovic; Mihaela Lazovic (UTMS Journal of Economics, 2016)
Heterogeneity and complexity determine multidisciplinary approach to the hospitality research. Identification and analysis of limited hospitality development factors imply very complex scientific approach. Case study methodology is applied on Republic of Serbia, which is transition country and candidate for EU accession. Research results identified key factors which had impact on lag, stagnation and contemporary level of hospitality development. Firstly, way of executed privatization process of hospitality companies in Serbia i.e. only ownership transformation, as part of business transformation, was done (organizational, management, technological, financial and human resources parts of business transformation didn't implement). Secondly, non-acceptable terms and conditions of credit lines for financing privatization and future business of privatized hospitality companies. Furthermore, buyers of privatized hospitality companies didn't prepared adequate projections of cash flow and sources of financing (owned and borrowed). Finally, technological development and human resources were result of the first mentioned limited factor. In order to improve business in hospitality industry in transition economies, all stakeholders should be involved. State should improve business environment. Educational institutions should create applicable programs on market. Investors should be ready to invest in technological and human resource development. Banks should implement the best financing practice from headquarters in EU.
Keywords: L83; P31; Z32; G32; 330; privatization; investment; finance; human resources